Perempuan-perempuan yang Memahkotai Kelamin Dengan Sastra - Indradi, Agustinus (Perspektif, 2006)
In many traditional communities, sex is considered a unsuitable subject to discuss or at least to talk about openly. This notion is in fact still intact in Indonesia, including among urban communities. Therefore, when sexuality is chosen to be the theme of a novel, moreover written by a woman, it becomes a subject of controversy and raises a lot of open debate and polemic. Apart from many objections, some Indonesian woman writters keep the subject alive in modern Indonesian literature. The author highlights the potrait of "genitals" from insight of women writters. Some are phylosophical, some are more touching the reality of life. The author also presents the idea of gender inequality in the area of literature. In the past it was dominated by male writters, so the recent appearance of some woman writters becomes an interesting phenomenon in Indonesian literature.